Intrauterine growth of a selected group of Peruvian twins - Ticona Rendón, Manuel (2015)
Newborn (RN) twin is at high risk for morbidity and mortality. It is classified with intrauterine growth curves (CCIU) single fetuses, but no Peruvian curves for this group. To determine the intrauterine growth of a selected group of Peruvian twins and compare RN unique patterns. MATERIALS AND METHODS: Descriptive, transversal study for 13 years (1992-2004) in the Hipolito Unanue Hospital in Tacna, Peru. 518 twins, 282 twins (54%) was selected without factors qie altered intrauterine growth. averages, standard deviation and percentiles 10, 50 and 90 of weight, height and head circumference was found for gestational age of 32-41 weeks, which were corrected with second order polynomial. Average percentile values and unique curvy compared RN, were considered significant when p <0.05. RESULTS: Of 36 909 live births, 518 were twins, which was selected 282. The most representative group was 38 weeks (10th and 90th percentiles of weight were 2275 and 3180 g, size, 45.8 and 48, 4 cm and head circumference, 323 and 354 mm, respectively. Compared to twin with the only RN at week 38, the difference in the p50 weight was 452g. Of the somatometric parameters studied, the weight was the most affected (44, 3%) of twins was located under the m10 curve weight of twins with RN unique, the behavior was similar until week 34, after which growth deteriorated significantly. In classifying the twins RN, found PEG frequency of 12%, which increases to 37% with only RN curves CONCLUSION:... The curves of intrauterine growth of twins differ significantly from growth RN is recommended to use only specific tables for twins to adequately evaluate their intrauterine growth.